Manipulative Materials for Discovering and Decomposing Numbers: Flashcards to Develop Number Sense - Fernández Bravo, José Antonio (Educación y Futuro: Revista de Investigación Aplicada y Experiencias Educativas, 2019)
This paper gathers reasons to support that the longer students are exposed to the counting technique the better their number sense will be. The basic principles for the acquisition of the number sense without the need to count are outlined and a set of manipulative materials is presented. These are number flashcards to perceive, differentiate and associate groups of objects, understand numbers up to 10, the concepts of equality and equivalence, composition, decomposition, addition and subtraction. These flashcards might increase action both in the frontal and the parietal lobes, thus improving students’ intellectual mathematical activity. Moreover, they stimulate emotion, creativity, reasoning and calculation, as they are the necessary functions for the further development of numerical and mathematical thought.